Characterization of an Estrogen Receptor α-Selective 18F-Estradiol PET Tracer - Sluka, Pavel; Ackermann, Uwe; Rigopoulos, Angela; Wardan, Hady; Pezaro, Carmel; Burvenich, Ingrid J.G.; Scott, Andrew M.; Davis, Ian D. (World Journal of Nuclear Medicine, 2024)
Objective Conventional imaging of cancer with modalities such as computed tomography or magnetic resonance imaging provides little information about the underlying biology of the cancer and consequently little guidance for systemic treatment choices. Accurate identification of aggressive cancers or those that are likely to respond to specific treatment regimens would allow more precisely tailored treatments to be used. The expression of the estrogen receptor α subunit is associated with a more aggressive phenotype, with a greater propensity to metastasize. We aimed to characterize the binding properties of an 18F-estradiol positron emission tomography (PET) tracer in its ability to bind to the α and β forms of estrogen receptors in vitro and confirmed its binding to estrogen receptor α in vivo.Methods The 18F-estradiol PET tracer was synthesized and its quality confirmed by high-performance liquid chromatography. Binding of the tracer was assessed in vitro by saturation and competitive binding studies to HEK293T cells transfected with estrogen receptor α (ESR1) and/or estrogen receptor β (ESR2). Binding of the tracer to estrogen receptor α in vivo was assessed by imaging of uptake of the tracer into MCF7 xenografts in BALB/c nu/nu mice.Results The 18F-estradiol PET tracer bound with high affinity (94 nM) to estrogen receptor α, with negligible binding to estrogen receptor β. Uptake of the tracer was observed in MCF7 xenografts, which almost exclusively express estrogen receptor α.Conclusion 18F-estradiol PET tracer binds in vitro with high specificity to the estrogen receptor α isoform, with minimal binding to estrogen receptor β. This may help distinguish human cancers with biological dependence on estrogen receptor subtypes.
Keywords: estrogen receptor α; estrogen receptor β; positron emission tomography; radiopharmaceuticals; competitive binding